Designing Tebing Tinggi City Hotel with Regionalism Architecture Approach - Harisdani, Devin Defriza; Santoso, Nailah (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Tebing Tinggi City has a strategic position outlined in the RPJMD 2011-2016, with a cross-Sumatra road network connecting Medan, Parapat, and Medan-Rantau Prapat and Medan-Siantar railroad networks. Kuala Namu Airport, Tebing Tinggi-Kuala Namu toll access, Kuala Tanjung International Port, and Sei Mangke industrial area encourage development. The RPJP vision of Tebing Tinggi City as a "City of Services and Trade with Quality Human Resources" supports the design of hotels with typical souvenir sales facilities. Tebing Tinggi City is famous for souvenirs such as Lemang, Roti Kacang, Halua, Kain Ulos, and handicrafts. By designing a hotel as a stopover, souvenir display facilities, and a specialty food court, the city has the potential to become an attractive destination for tourists. Although it does not yet have adequate lodging and souvenir shopping facilities, designing a 3-star hotel is a solution to improve economic services and visitor attraction. Regionalism architecture can be applied with local materials such as wood and stone and design elements from local Malay architecture, considering tropical climate aspects for comfort. This approach will embody the richness of local culture and nature, provide memorable experiences for visitors, and strengthen regional identity and economy.